(untitled) (Biological Sciences - PJSIR, 2001)
Aqueous and methanolic extracts of the leaves, seeds and stem bark of Hunteria umbel/ala. K. Schum, were tested for anthelmintic activity. The extracts of the leaves, seeds and stem bark have significant anthelmintic activity when compared with normal saline which acted as control. The methanolic extract of the stembark had the highest activity for all the extracts. However, the activity of the aqueous extract of the seeds was more effective than the aqueous extract of the leaves and stembark.